简单化简下就有了。
对函数y=Asin(ωx+φ),若φ=kπ,
k为偶数2n时,y=Asin(ωx+2nπ)=Asin(ωx)是奇函数;
k为奇数2n+1时,y=Asin(ωx+2nπ+π)=Asin(ωx+π)=-Asin(ωx)还是奇函数。
所以,φ=kπ时,y=Asin(ωx+φ)是奇函数。
对函数y=Asin(ωx+φ),若φ=kπ±π/2,以φ=kπ+π/2为例说明。
k为偶数2n时,y=Asin(ωx+2nπ+π/2)=Asin(ωx+π/2)=Asin(π-(ωx+π/2))=Asin(π/2-ωx)=Acos(ωx),是偶函数;
k为奇数2n+1时,y=Asin(ωx+2nπ+3π/2)=Asin(ωx+3π/2)=-Asin(ωx+π/2)=-Acos(ωx),是偶函数。
所以,φ=kπ±π/2时,y=Asin(ωx+φ)是偶函数。
对函数y=Acos(ωx+φ),若φ=kπ,
k为偶数2n时,y=Acos(ωx+2nπ)=Acos(ωx)是偶函数;
k为奇数2n+1时,y=Acos(ωx+2nπ+π)=Acos(ωx+π)=-Acos(ωx)还是偶函数。
所以,φ=kπ时,y=Acos(ωx+φ)是偶函数。
对函数y=Acos(ωx+φ),若φ=kπ±π/2,还是以φ=kπ+π/2为例说明。
k为偶数2n时,y=Acos(ωx+2nπ+π/2)=Acos(ωx+π/2)=-Acos(π-(ωx+π/2))=-Acos(π/2-ωx)=-Asin(ωx),是奇函数;
k为奇数2n+1时,y=Acos(ωx+2nπ+3π/2)=Acos(ωx+3π/2)=-Acos(ωx+π/2)=Asin(ωx),是奇函数。
所以,φ=kπ±π/2时,y=Acos(ωx+φ)是奇函数。
这个问题不难,可以简单化